Early implant placement and peri-implant augmentation with a porcine-derived acellular dermal matrix and synthetic bone in the aesthetic area: a 2-year follow-up prospective cohort study. Issue 2 (February 2021) - Papi, P.; Pranno, N.; Di Murro, B.; Pompa, G.
Abstract: The aim of this study was to evaluate the 2-year follow-up results of early implant placement with simultaneous peri-implant augmentation using an acellular dermal matrix (ADM) and a synthetic bone substitute in the aesthetic zone. Twenty subjects were enrolled in this study, they were either males (eight) or females (12), with a mean age of 47.8 ± 4.45 years and each patient was treated with one implant. Simultaneous contour augmentation with guided bone regeneration was performed using synthetic bone particles (maxresorb®) and an ADM (mucoderm®). Keratinized mucosa width (KMW) and gingival thickness (GT) were assessed at baseline, 1, 3, 6, 12 and 24 months. Marginal bone loss, probing pocket depth, bleeding on probing and plaque index were also recorded. GT and KMW increased between baseline and 1 month, slightly decreased between 1 month and 12 months ( P  < 0.001) and remained stable between 12 and 24 months ( P  < 0.001). After 2 years, mean marginal bone loss level was 0.51 ± 0.63 mm, with no probing pocket depth values >5 mm and no concomitant signs of inflammation registered. Pink aesthetic score was 8.3. Combining an ADM and guided bone regeneration with early implant placement revealed a significant increase of 1.9 mm for GT and 1.6 mm for KMW after 2 years, showing good patient satisfaction regarding the aesthetic outcomes of soft tissues and prosthetic crown.